2011
DOI: 10.1074/jbc.m110.212571
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of a Full-length Retroviral Integrase Monomer and Dimer, Revealed by Small Angle X-ray Scattering and Chemical Cross-linking

Abstract: We determined the size and shape of full-length avian sarcoma virus (ASV) integrase (IN) monomers and dimers in solution using small angle x-ray scattering. The low resolution data obtained establish constraints for the relative arrangements of the three component domains in both forms. Domain organization within the small angle x-ray envelopes was determined by combining available atomic resolution data for individual domains with results from cross-linking coupled with mass spectrometry. The full-length dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
38
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 63 publications
(69 reference statements)
5
38
0
Order By: Relevance
“…We recently employed small and wide angle x-ray scattering (SAXS/WAXS) in combination with chemical cross-linking to elucidate the full-length architecture of the apoIN monomer and dimer of ASV (3). We showed that the ASV IN dimer derives its stability from interactions of the NTD of one monomer with the CTD and core of the second monomer and from CTD-CTD contacts between the monomers; core-core interactions are only observed in tetramers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We recently employed small and wide angle x-ray scattering (SAXS/WAXS) in combination with chemical cross-linking to elucidate the full-length architecture of the apoIN monomer and dimer of ASV (3). We showed that the ASV IN dimer derives its stability from interactions of the NTD of one monomer with the CTD and core of the second monomer and from CTD-CTD contacts between the monomers; core-core interactions are only observed in tetramers.…”
mentioning
confidence: 99%
“…Integration of retroviral DNA into the host cell genome is an essential step in viral replication catalyzed by the viral integrase (IN) 3 protein (for a recent review, see Ref. 1).…”
mentioning
confidence: 99%
“…While not impossible, we favor the straightforward interpretation that 3′ processing activity is catalyzed by the integrase tetramer in the context of the SSC during viral infection. Of note, results of small angle X-ray scattering (SAXS) have yielded novel "reaching dimer" solution conformations for full-length HIV-1 and ASLV integrase in the absence of DNA (137,138). Although extensive CTD-CTD interactions preclude these structures from functionally engaging DNA, they nevertheless could represent intermediates on the pathway to SSC formation (see the chapter by Anna Marie Skalka).…”
Section: Integrase Functions As a Multimermentioning
confidence: 99%
“…There are strong structural similarities in the CCD between HIV, PFV and RSV IN (Figure 2) [47,51,52,57,67,76,77] suggesting that under appropriate conditions the highly soluble RSV IN could also be trapped in the presence of the appropriate oligonucleotide (ODN) substrate and STIs. Assembly of a trapped RSV SC at high IN concentrations (1.5 mg/mL; 45 µmol/L) in solution required the presence of 3' OH recessed viral ODN ranging in sizes (16/18R to 18/20R) and DTG, RAL or MK-2048 [50] (Figure 9).…”
Section: Hiv and Rsv Synaptic Complexes Are Kinetically Stabilized Bymentioning
confidence: 99%
“…PFV IN is soluble (10-15 mg/mL) in 0.2 mol/L NaCl [48,49] while RSV IN is highly soluble (30 mg/mL) in 0.2 mol/L (NH4)2SO4 [50] . PFV IN is monomeric [49] while RSV IN is a dimer in solution [50][51][52] . Recombinant HIV IN has been purified as a monomer, dimer and tetramer [47,53,54] .…”
Section: Solution Properties Of Inmentioning
confidence: 99%